Contemplation of the possibility of extending the shelf life of human immunoglobulin reference standard used for determination of anticomplementary activity - O. G. Kornilova; M. A. Krivykh; E. A. Husnatdinova; E. S. Konovalova; R. A. Volkova; O. V. Fadeykina; E. Yu. Kudasheva; A. A. Movsesyants (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article gives an account of the stability study performed for two batches of human immunoglobulin reference standard (RS) used for determination of anticomplementary activity (industry reference standard, IRS 42-28-430). The first batch of human immunoglobulin reference standard used for determination of anticomplementary activity showed sustainable results during 30 months of storage at (5±3) °C which makes it possible to extend the RS shelf life from 18 months (corresponding to the initial monitoring period) to 30 months from the date of determining the certified parameter, given the acceptable range of more than 50 % for the positive control and less than 50 % for the negative control. Based on the results obtained, the re-certification was performed for the second RS batch after 18 months of storage. The main certified parameter (anticomplementary activity) of the negative control was within the range of 41.6±7.2 %, and of the positive control 75.7±6.8 % for the confidence level of 0.95. Therefore, the shelf life of the second batch of the human immunoglobulin reference standard used for determination of anticomplementary activity (IRS 42-28-430) was extended until February 2018, which makes 30 months.